(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Travelicious Travel Agency is a commercial enterprise where travelers can get secure information and impartial counseling from experts, whether they choose to travel via air, sea, or land. Travelicious also offers other services such as business travel, which helps entrepreneurs to plan and book their conferences and meetings. Given that travel agencies are trained to give advice on destinations worldwide, the target market of the study includes individuals from schools and nearby banks, as well as the residents of the area. Travelicous Travel Agency has an office along North Fairview Novaliches, Quezon City, and this office has an area of 25.1 m. The lobby has three areas. The location is ideal because the commuting public will be able to see the business. Imagine going to work or coming home from work tired and hungry for a break from all the stress and seeing the offers of Travelicious Travel Agency. Moreover, an additional boost for the location will be the impending completion of the MRT-7, which will provide more audience to view Travelicious Travel Agency’s offers. The location is also near some schools, banks, and several subdivisions and establishments, which can also be potential sources of clients. The proponents did observations on the proposed business site and initiated a random survey for 50 people composed of students, employees, and housewives. According to the survey, 50% are male respondents, while 50% are female. A total of 70% of the respondents travel thrice a year. Respondents prefer Iloilo as a travel destination, with ideal yearly budget of P10,000. For respondents, 80% said that home lodging is the most ideal place to stay at when travelling. The expected return of investment on its first-year operation is 35.14%, followed by the next ROI of the business. The findings showed that Travelicious Travel Agency is feasible and viable to the market. Meanwhile, the researchers’ business stall must keep on promoting the business through the social media because many people are now actively engaged in technology through the use of social media. The researchers concluded that to keep up with competition not only from other agencies but also on the business demand, online travel booking should be patronized with some unique and appealing measures to attract possible clients. Therefore, it is recommended to adapt the modern measures and bolster the quality and appeal of the services offered. Nevertheless, to introduce new and fresh ideas that will promote and reintroduce clients to classic and native ways, the immersion package will encourage a more comprehensive and close-up experience with the locals. The researchers’ financial must keep on increasing their revenue each year to have a return on investment within five years efficiently.